The Politics of Minimum Wage in Nigeria: The Unresolved Issues - NWUDE, E Chuke (Asian Journal of Empirical Research, 2013)
One of the duties of government is to ensure the welfare of her citizens. This is also reflected in Nigerian constitution in Section 14(b) of the 1999 constitution which states that the security and welfare of the people shall be the primary purpose of government. One way through which attempt has been made to address the issue of welfare is the legislation of a national minimum wage. In this direction, between 1934 and 2011, many commissions and committees had been set up to undertake either a holistic or partial review of salaries and wages in the public service. This was in apparent realization that the workers could no longer survive on what they earn, since those who work also have to support their families who form part of the huge army of the unemployed. Though, these reviews did not come without intense agitation by the workers but the question has been, after all these protocols, is the welfare of the citizens maximized through decent standard of living. Through archival and field study research it was discovered that wage reviews were largely not structured to address the basic needs of the workers. This has led to frequent strike actions by workers aimed at getting government to agree to negotiate a new minimum wage and a general upward review of wages. Inflation continues intensifying with the disproportionate cost of foods and living index increasing. Consequently, the erosion in the real wages and salaries of workers is alarmingly severe.Conclusively the prevailing minimum wages paid by the three tiers of government are grossly inadequate compared to the sustainable budgets for all the family income levels as well as the international benchmarks of the United Nations.